Unconventional site of pacing for failed balloon valvotomy of prosthetic tricuspid valve: a case report - Aditi Newaskar; Radha Nandipati; Somasekhar Ganta; Dharma Teja Dhulipalla; John Satish; Krishna Prasad Nevali (The Egyptian Heart Journal)
Abstract Background Conduction disturbances are a frequent occurrence after tricuspid valve surgeries, and their management is challenging. Case presentation We present a case of 16-year-old male patient who presented with episodes of presyncope. At the age of 7 years, he underwent tricuspid valve replacement surgery with a biological prosthesis for infective endocarditis sourced from a gluteal abscess. Post-operatively, he had complete atrioventricular block and underwent epicardial pacing. Epicardial lead impedance increased at follow-up and led to failure of pacing. At the time of presentation he had prosthetic tricuspid valve dysfunction with increased gradients. We did tricuspid valve balloon valvotomy but the gradients did not improve and patient developed tricuspid regurgitation. In view of difficulty in placing the lead through degenerated tricuspid valve, we have decided to place the lead in coronary sinus. He underwent successful lead placement in posterolateral tributary of coronary sinus with acceptable parameters. He had an uneventful follow-up at 1 year. Conclusion TV surgeries create a unique problem for pacing. Coronary sinus pacing offers an effective alternative to conventional RV pacing in such cases.